Social support and physical exercise: The mediating role of achievement emotions, and the moderating role of exercise motivation and feedback literacy - Hui Zhang; Yuzhong Zhang; Yi Zhou; Baichao Xu (PLoS ONE, 2025)
Objective While research on physical exercise has predominantly focused on rational decision-making behaviors related to health benefits, comparatively less attention has been paid to achievement emotion and its role in promoting physical exercise. Building upon dual-system theory (DST), this study examines whether achievement emotion mediates between social support and physical exercise, integrating expected value and information processing theories. It also explores how this mediation effect depends on sports motivation and feedback literacy. Methods A questionnaire survey was conducted among 534 college students (281 male, 253 female). Data were analysed using hierarchical regression procedures in terms of moderated mediation. Results The results show that achievement emotion partially mediates the relationship between social support and physical exercise. Specifically, the interaction of social support × sports motivation indicates that the strength of the relationship between social support and achievement emotion increases linearly with higher levels of sports motivation; similarly, the interaction of social support × feedback literacy indicates that the strength of the relationship between social support and physical exercise also increases linearly through feedback literacy level. Finally, the interaction of achievement emotion × feedback literacy indicates that the strength of the relationship between achievement emotion and physical exercise increases linearly through feedback literacy level. Conclusions These findings suggest that attention should be paid to achievement emotion, sports motivation, and feedback literacy when designing social support interventions to promote physical exercise. This research provides a theoretical reference for improving levels of physical exercise among college students.